"Clean, safe and orderly": Migrants, race and city image in global Guangzhou. (March 2018) - Wilczak, Jessica
This paper examines an urban renewal project in Xiaobei, a neighborhood that has become a gathering place for African traders in the Chinese city of Guangzhou. Drawing on documentary analysis, interviews and site visits, the paper argues that, while there is a racial element to the project, we should be careful about ascribing it solely to anti-black racism. The project is as much characterized by pejorative discourses about internal migrants as it is about Africans. Moreover, the project is not unique to Xiaobei, and should also be understood in the context of Guangzhou's efforts to become a competitive "global" city.